Spatial differences, distribution dynamics and driving factors of the synergy between marine ecological security and high-quality development in three major marine economic circles of China - Ni, Ran; Guan, Hongjun; Wang, Yichuan; Liu, Yilin (Frontiers in Marine Science, 2024)
Exploring the regional differences in the synergy between marine ecological security (MES) and high-quality development of the marine economy (MHQD) and its driving mechanism is the key to optimizing the spatial distribution of marine development, promoting the synergistic and balanced development of the regional marine composite system during the "14th Five-Year Plan" period. In this study, we construct a mechanistic framework for the coupling and coordination of the MES-MHQD composite system, and reveal the evolution of regional differences, sources, and distributional dynamics of synergistic development of the composite system from 2009 to 2020. Meanwhile, spatial econometric analyses are applied to identify the influencing factors and spatial spillover effects. The results show that the level of synergistic development of composite system has a fluctuating upward trend, with a significant positive spatial correlation and a significant "polarization effect". Inter-regional differences in the synergistic development of the composite system are the main source of the overall differences. Factors such as innovation-driven, human capital, and opening up to the outside world are important driving factors for the synergistic development of the composite system. The study provides a theoretical basis and decision-making reference for the promotion of the synergistic development of the composite system of the Three Major Marine Economic Circles (3MMECs) in China.